The stroke length, frequency and velocity among univesity physical education students and its use as a pedagogical tool - Stallman, R. K.; Kjendlie, P. L. (Biomechanics and Medicine in Swimming X, 2006)
This study examined the relationship between stroke length, frequency and velocity among non-competitive young adult swimmers. In a test -retest design, the stroke length, frequency and velocity triad was examined for a 50 meter crawl maximum effort. A focus on stroke length as a pedagogical tool was examined for its effect over a 12 week period. The elementary back stroke was introduced early to initiate the subjects in the concept of stroke length and TLT2 sub-maximal trials were also conducted. Fifty university students participated. Results of a paired t-test analysis showed a significant improvement in time, a significant increase in stroke length and a less significant decrease in frequency.